Implementation of the Media Art Journal to Improve Emotional Regulation in 4–5-Year-Old Children - Nabilla Fasya Amelindha; Neneng Tasu'ah (Prodi PG-PAUD, FKIP, Universitas Trilogi, 2026)
Emotional regulation problems in early childhood are still frequently observed, such as children crying easily, becoming angry, withdrawing, and having difficulty expressing feelings verbally. These conditions indicate that children require emotional stimulation appropriate to their developmental stage. This study aimed to describe the implementation of art journal media in improving emotional regulation among children aged 4–5 years at TK Pembina ABA 54 Semarang. The study employed a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation, with three classroom teachers serving as the primary informants. Data analysis utilized the Miles and Huberman model, encompassing data reduction, data display, and drawing conclusions. The findings revealed that art journal activities were implemented through drawing, coloring, storytelling, and simple emotional reflection. Following routine implementation, the children became calmer, more communicative, better able to express their feelings verbally, and more capable of controlling their emotional reactions. Teachers also served as emotional facilitators by providing emotional validation and guidance during the activities. The study concludes that art journaling is effective in fostering emotional regulation in early childhood because it offers a safe and enjoyable space for emotional expression.